Achieving resist against DHCP man-in-the-middle attack scheme based on key agreement - Zhiqiang YAO; Zhirong ZHU; Guohua YE (Tongxin xuebao)
In order to deal with the issue of the man-in-the-middle attack in the process of using dynamic host configuration protocol, a lightweight scheme was proposed.A new key agreement algorithm was developed based on public key cryptography to generate relevant keys, reducing the key storage burden.On the basis, a secure scheme was proposed, where two-way authentication of participants was designed to prevent the man-in-the-middle attack and digital signatures conforming to protocol specifications was constructed to ensure the legitimacy of the message source.By security analysis, the proposed scheme was demonstrated to be secure and valid against the man-in-the-middle attack and other common attacks.Experimental results show that the proposed scheme has the better performance compared with the related schemes, and can be compatible with both DHCPv4 and DHCPv6.